2022
DOI: 10.1186/s12889-022-13315-5
|View full text |Cite
|
Sign up to set email alerts
|

Self-reported injuries and correlates among school-going adolescents in three countries in Western sub-Saharan Africa

Abstract: Background Unintentional injuries among adolescents constitute a significant public health problem globally. Injured adolescents may face negative outcomes ranging from poor academic performance to short- and long-term physical and psychosocial health struggles, and even death. The aim of this study was to estimate the prevalence and describe the correlates and most frequent causes of injuries among school-going adolescents in three West African countries – Benin, Ghana, and Liberia. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…An India cross-sectional study shown that the sickness absenteeism of unintentional injuries averaged over one week, and about half of injured children missed school after an injury [ 34 ]. Students who are more frequently absent from school have missed teacher-led lessons, peer interactions, and other learning activities, and are consequently likely to obtain lower academic performance [ 35 37 ]. With regard to intentional injury, we found that psychological health problems including internalizing and externalizing behaviors were negatively associated with academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…An India cross-sectional study shown that the sickness absenteeism of unintentional injuries averaged over one week, and about half of injured children missed school after an injury [ 34 ]. Students who are more frequently absent from school have missed teacher-led lessons, peer interactions, and other learning activities, and are consequently likely to obtain lower academic performance [ 35 37 ]. With regard to intentional injury, we found that psychological health problems including internalizing and externalizing behaviors were negatively associated with academic performance.…”
Section: Discussionmentioning
confidence: 99%
“…A similar prevalence of serious injuries has been reported in Polynesia (43.1% on Cooks Island, 40.8% in Niue and 49.1% in Tonga) [ 3 ]. In addition, Ghana has reported a similar prevalence (46.1%) of serious injuries among in-school adolescents using a national representative sample [ 21 ]. The current finding is also similar to the overall prevalence of serious injuries found in among adolescents in Malaysia [ 26 ] and four Southeast Asian countries (Indonesia, Myanmar, Sri Lanka, and Thailand) [ 25 ], which reported prevalence below 50 per cent.…”
Section: Discussionmentioning
confidence: 99%
“…A set of explanatory variables including socio-demographic characteristics (age and sex), mental health variables (anxiety, loneliness and suicidal behaviours), socio-environmental factors (hunger, bullying, physical attack, fighting, tobacco use, cigarette smoking, truancy, and having close friends) and parental factors (supervision, connectedness, knowledge of activity and privacy) were used in the current study based on their relevance in influencing adolescents’ health-related behaviours [ 5 , 9 , 25 , 26 ].…”
Section: Methodsmentioning
confidence: 99%
“…The prevalence rates vary by country with school-going adolescents in These variations in the prevalence of substance use among school-going adolescents can be attributed to variations in the risk and protective factors of substance use within SSA countries. For example, multi-country studies in SSA have reported variations in risk factors for substance use such as bullying victimization [9], serious injuries [5,26], truancy [25] and suicidal behaviours [19,24]. Specifically, Seychelles has large tourist visits from western countries with liberal attitudes and practices regarding substance use including alcohol and marijuana which could influence school-going adolescents through observational learning.…”
Section: Prevalence Of Alcohol Marijuana and Amphetamine Use Among Sc...mentioning
confidence: 99%